2017
DOI: 10.1523/jneurosci.3618-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and Acute Stress Promote Overexploitation in Serial Decision Making

Abstract: Many decisions that humans make resemble foraging problems in which a currently available, known option must be weighed against an unknown alternative option. In such foraging decisions, the quality of the overall environment can be used as a proxy for estimating the value of future unknown options against which current prospects are compared. We hypothesized that such foraging-like decisions would be characteristically sensitive to stress, a physiological response that tracks biologically relevant changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 39 publications
4
73
0
Order By: Relevance
“…Various neurobehavioral despair such as anxiety, depression, compulsive behaviours and loss of cognitive functions precipitated by various stresses have already been described (Kumar et al 2011;Chanana and Kumar 2016;Petit et al 2016;Lenow et al 2017;Mataix-Cols et al 2017;Perez et al 2017;Zhukovsky et al 2017). We also observed reduction in the spontaneous motor activity along with a concomitant increase in immobility time in the FST and TST which reflects a state of behavioural despair.…”
Section: Discussionsupporting
confidence: 80%
“…Various neurobehavioral despair such as anxiety, depression, compulsive behaviours and loss of cognitive functions precipitated by various stresses have already been described (Kumar et al 2011;Chanana and Kumar 2016;Petit et al 2016;Lenow et al 2017;Mataix-Cols et al 2017;Perez et al 2017;Zhukovsky et al 2017). We also observed reduction in the spontaneous motor activity along with a concomitant increase in immobility time in the FST and TST which reflects a state of behavioural despair.…”
Section: Discussionsupporting
confidence: 80%
“…Recent work in humans further resolves the computational challenge of learning dynamic environmental richness, by demonstrating that sequential choice behavior is best captured by an MVT inspired learning model. Specifically, both decisions to leave a patch and explore the environment in patch foraging (Constantino and Daw, 2015;Lenow et al, 2017) and capture behavior in prey selection (Garrett and Daw, 2019) adhere to the MVT predicted optimality policy that compares yields against fluctuating environmental richness which is learned via a standard delta rule. This later work further demonstrated that beliefs about environmental richness update with asymmetric bias, whereby improvements are learned at a higher rate than deteriorations; the 'naïve perseverance of optimism' (Garrett and Daw, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, contexts like the boom and downturn examples above rarely remain in steady-state, further requiring perturbation-driven behaviour adjustments. Recent work in humans resolves both issues, by demonstrating that sequential choice behaviour is best captured by an MVT inspired learning model (Constantino & Daw, 2015;Garrett & Daw, 2019;Lenow, Constantino, Daw & Phelps, 2017). Specifically, the decision to depart one patch of potential resources to harvest in another during a dynamic patch foraging task is predicated on a leave threshold, defined as the harvest sacrificed when leaving.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations